Accounting, performance and accountability challenges in hybrid organisations: a value creation perspective. Issue 3 (15th December 2021) - Grossi, Giuseppe; Vakkuri, Jarmo; Sargiacomo, Massimo
Abstract : Purpose: Drawing upon theoretical insights on value creation perspectives, the authors aim to advance the understanding of performance and accountability in different hybrid organisations. Design/methodology/approach: The authors conceptualise common theoretical origins of hybrid organisations and how they create and enact value, by reflecting on the Accounting, Auditing and Accountability Journal (AAAJ) special issue articles. Furthermore, the authors propose an agenda for future research into accounting, performance and accountability for hybrid organisations. Findings: Hybrid organisations can be conceptualised through their approaches to value creation (mixing, compromising and legitimising). This article provides a more detailed understanding of accounting, performance and accountability changes in hybrid organisations. Practical implications: This contribution also has relevant practical implications for actors, such as politicians, managers, professionals, auditors, controllers and accountants, encased in various hybrid organisations, policy contexts and multi-faceted interfaces between public, private and civil society. Originality/value: Hybridity lenses reveal novel connections between different types of hybrid organisations and how they create and enact multiple values.